SOSIALISASI SENAM HAMIL BIRTH BALL DALAM KELAS IBU HAMIL PADA BIDAN - Wenny Indah Purnama Eka Sari; Yusniarita Yusniarita (P3M Universitas Aisyiyah Surakarta, 2021)
Midwives who are at the forefront of maternal and child health services, must have knowledge, skills and attitudes to be continuous and increasing. One of the innovations that can be applied in antenatal class is pregnancy exercises use of birth ball. Pregnancy exercises use of birth ball is physical exercise therapy for pregnant women use of birth ball as a tool to improve comfort and fitness during pregnancy. Socialization of pregnancy exercises use of birth ball for midwife purpose to increase the knowledge of midwives about the benefits of birth ball and improve the skills of midwifes in providing maternity care to pregnant women so that midwives can teach pregnant women pregnancy exercises use of birth ball . The obvective of this activity is midwives who are directly involved in maternal and child health services and pregnant womenz. The conclusion is socialization of pregnancy exercises use of birth in antenatal class for midwifes is well. Midwifes understand about benefit use of birth ball and can teach pregnant women pregnancy exercises use of birth ball.